Biometric, physical-chemical, bioactive and antioxidant components in araçás at different maturation stages (Research, Society and Development, 2020)
The araçá (Psidium cattleianum) belongs to a class of fruits widely distributed in the Brazilian territory presenting different species. Although still little explored, research reports the presence of bioactive compounds in the composition of the species, attributing to these fruits nutritional and functional properties. In this work, the physical, physical-chemical aspects, bioactive compounds and the antioxidant capacity of araçá at different maturity stages were evaluated. The evaluations were carried out in the Laboratory of Technology of Products of Vegetable Origin of the Center of Sciences and Technology of Food of the Federal University of Campina Grande, in the Campus of Pombal - PB. The fruits came from plantations located in the city of Areia - PB, being harvested directly in the top of the plant, taking the color of the bark as the harvest index. The experimental design used was completely randomized (p˂0.05). Physico-chemical characteristics of soluble solids, total soluble sugars and the SS / AT ratio, increased with advancing maturation. For bioactive compounds, the ascorbic acid content increased considerably and a reduction in the flavonoid content was observed with advancing maturation. The phenolic compounds showed maximum values in the fruits in stage I and a reduction of more than 50% for stage IV, as well the ability to reduce the DPPH radical decreased with advancing maturation. As the results it is possible to conclude that the evaluated araçás, independent of the maturation stages, presented considerable amounts of biologically active compounds, being able to constitute as a good source of natural antioxidants.